Features and Trends of Social Sciences Applied to Sport in the Italian Context - Irene Strazzeri; Giusi Antonia Toto (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
In Italy, initially the social sciences of Sport was considered a specialization to the macro-discipline of Sociology of leisure time, but today it boasts a tradition of pluriventennial studies. It is equally important to consider the number of this discipline among the studies on mass culture due to its extent of aggregating phenomenon. The purpose of this article is to examine the research trends of social sciences applied to sport in the Italian context. From a methodological point of view, a systematic review of the existing literature will be provided following the PRISMA guidelines both on the main research currents and on the main emerging topics in the contemporary specialist literature. Comparing application studies and empirical experiences, it can be suggested that the social sciences in Italy with an international scientific tradition play a key role in research applied to sports by specializing research tendencies towards specific topics of study.